2013
DOI: 10.1179/1351000213y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

Serum malondialdehyde levels, myeloperoxidase and catalase activities in patients with nephrotic syndrome

Abstract: We concluded that serum MPO activity and oxidative stress were increased and that serum catalase activity was decreased in patients with adult nephrotic syndrome. In addition, these results indicate that increased MPO activity is associated with an oxidant-antioxidant imbalance that may contribute to atherosclerosis in patients with adult nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…We also showed that 3‐AT significantly increased plasma MDA level (Fig. B ), which is consistent with higher plasma MDA in patients with lower catalase activity (Begenik et al., ). Notably, the inconsistency between lower myocardial and higher plasma MDA levels following 4‐MP, 3‐AT, or their combination (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…We also showed that 3‐AT significantly increased plasma MDA level (Fig. B ), which is consistent with higher plasma MDA in patients with lower catalase activity (Begenik et al., ). Notably, the inconsistency between lower myocardial and higher plasma MDA levels following 4‐MP, 3‐AT, or their combination (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with published data showing improved endothelial function 24 hours after levosimendan treatment 18 , as leukocyte activation and especially MPO activity can significantly impair endothelial function 8 . Avgeropoulou and colleagues have found a decrease in MDA, a marker of oxidative stress, at day 5 after levosimendan treatment 26 , which supports our hypothesis of diminished PMN degranulation and MPO activity after levosimendan treatment, as MPO activity and MDA-levels usually correlate well 27 .…”
Section: Discussionsupporting
confidence: 86%
“…An increased activity of NOX through increased expression of NOX gene in patients with INS would indicate higher cellular oxidative stress in PBL that may impair the structure and function of blood lymphocytes to compromise the immune system. Impairment of antioxidant enzymes such as catalase, myeloperoxidase, and SOD in plasma/serum of patients with INS has also been reported earlier (26). Increased levels of malondialdehyde, an index of lipid peroxidation, observed in our patients support earlier studies that suggest an increased cellular oxidative stress in NS.…”
Section: Discussionsupporting
confidence: 91%